Biocatalytic Synthesis of Chiral Benzylic Alcohols via Enantioselective Hydroxylation by a Self-Sufficient Cytochrome P450 from Deinococcus gobiensis - Cui, Hai-Bo; Ma, Ting; Zhang, Ru-Yue; Shan, Jing; Wang, Zhong-Qiang; Bai, Mei; Chen, Yong-Zheng (Synthesis, 2023)
Enzymatic asymmetric benzylic hydroxylation represents a green synthesis of valuable chiral benzylic alcohols. The stereoselective C–H direct hydroxylation profile possessed by cytochrome P450 monooxygenases (P450s) makes it more attractive. Here, we successfully expressed a self-sufficient cytochrome P450 monooxygenase from Deinococcus gobiensis in Escherichia coli BL21(DE3) host. The recombinant E. coli (P450DG) strain performed well in terms of functionality and has stereoselective benzylic hydroxylation ability for propylbenzene substrates. Asymmetric benzylic hydroxylation of various aromatic compounds was further investigated using the recombinant E. coli (P450DG) strain based on the optimal conditions, producing the corresponding enantioenriched pharmaceutically relevant benzylic alcohols in moderate yields with good to excellent enantioselectivity.
Keywords: biocatalysis; cytochrome P450; enantioselective hydroxylation; whole-cell bioconversion; chiral benzylic alcohols